Gambaran Pemberdayaan Pasien Gangguan Jiwa Di Pondok Nurussalam Demak Jawa Tengah - NOVITASARI, AFRIDA, Arif Widodo, A.Kep., M.Kes (2016)
Treatment for psychiatric patient do not always have to be done in a mental hospital by the help of doctors and nurses as well using chemical drugs. Treatment for psychiatric patients can also be done in other ways, namely by using the means of therapy and empowerment as well as performed in Pondok Pesantren Nurussalam. Empowerment in boarding schools is not done by a doctor or nurse, but it is done by care takers of the boarding schools. This study aimed to describe the process of empowerment of psychiatric patient conducted by Pondok Pesantren Nurussalam. The objects of this research were the soul's disorders patients and psychiatric patient stewards in Pondok Pesantren Nurussalam. Type of this research was a descriptive qualitative research. The techniques of collecting data used were observation, interviews, and documentation. Qualitative data analysis techniques used concepts from Miles and Hubermen. As the result, the researcher highlights several points i.e 1). The process of inclusion of psychiatric patients in Pondok Pesantren Nurussalam, 2). Placement of psychiatric patients and patients conditions in the first time enter the dormitory, 3). Classification of psychiatric patients and criteria of decent patients to be empowerment, 4). Empowerment activities which are flexible, 5). Effectiveness of psychiatric patients empowerment. Empowerment is one of the effective ways to treat psychiatric patients. This is because empowerment is done with the goal of keeping the patient to perform like other normal people should.